American foreign policy in regions of conflict : a global perspective - Wiarda, Howard J., 1939- (New York : Palgrave Macmillan, 2011)
"America's regional foreign policy priorities are shifting, toward Asia, the Middle East, Latin America, and Africa, and away from Europe and Russia. Wiarda examines these changes and the reasons for them in each of these regional areas in this comprehensive work on global perspective on American foreign policy. Designed as a text for introductory international relations, foreign policy, comparative politics, and world politics courses, this book succeeds in integrating these often separate subfields and shows how the study of comparative politics can enlighten foreign policy"--
Includes bibliographical references and index.
Keywords: Conflict management -- United States; United States -- Foreign relations -- 2009-